Equity of Bikeway Distribution in Minneapolis, Minnesota. Issue 1 (January 2017) - Wang, Jueyu; Lindsey, Greg
Governments and nonprofit organizations are investing in the bicycling infrastructure. However, the benefits of the bicycling infrastructure have not always been distributed equally among neighborhoods, and the equity of the distribution has been a major concern. This study used two measures, the Gini coefficient and the loss of accessibility to jobs via bikeways, to assess both the horizontal and the vertical equity of the bicycling infrastructure's distribution in Minneapolis, Minnesota. Gini coefficients, calculated from Lorenz curves, provide a single flexible measure that allows comparisons within and between groups. Determination of accessibility to jobs via lower-stress bikeway and street networks allows the levels of connectivity via bikeways to be compared for different groups. Minneapolis is making substantial investments in the bicycling infrastructure and was used as a case study because data with which to assess changes in equity over time are available. With use of the block group as the unit of analysis, systemwide analyses of the distribution of bikeways relative to the locations of the population and total employment revealed increases in equity from 2010 to 2014. Comparison of Gini coefficients for all bicycling facilities among different subpopulations demonstrated horizontal inequities within each subgroup as well as indicators of vertical equity for various disadvantaged subgroups. The Gini coefficients revealed inequities in the distribution of urban trails for disadvantaged subpopulations. With the use of 3-mi network buffers, a bikeway penalty, calculated as the loss of job accessibility resulting from the choice to rely on a bikeway rather than on street networks, demonstrated a vertical equity for disadvantaged subgroups. These measures can be used to inform planning for and investments in bicycling facilities and to assess and compare the bicycling infrastructures of cities.